The Relationship Between Social Justice Leadership and Work Engagement: The Mediating Role of Well-Being and the Moderating Role of Gender - Karabatak, Songul; Alanoglu, Muslim; Aslan, Serkan (Wiley, 2025)
The present research investigates the influence of school principals' social justice-oriented leadership on teachers' engagement with their work. Particular attention is given to the mediating effects of subjective and psychological well-being, as well as the moderating function of gender. Data were obtained from a sample of 492 public school teachers working in two provinces of T & uuml;rkiye during the 2023-2024 academic year, using a quantitative and correlational design. To evaluate the proposed relationships, structural equation modelling was conducted through Bayesian estimation with four established measurement tools. Findings reveal that social justice leadership is associated with improvements in both subjective and psychological well-being, which, in turn, fully mediate its impact on work engagement. Moreover, gender differences emerged, indicating that male teachers reported stronger well-being outcomes compared to female teachers when perceiving higher levels of social justice leadership. Overall, the study extends the job demands-resources model by illustrating leadership as a vital job resource and contributes to positive psychology literature by demonstrating the motivational role of well-being. These results highlight the importance of social justice leadership practices for enhancing teacher engagement and supporting their mental health.
Keywords: social justice leadership; teacher engagement; well-being